Byssinosis in carpet weavers exposed to wool contaminated with endotoxin. Issue 7 (July 1987) - Ozesmi, M; Aslan, H; Hillerdal, G; Rylander, R; Ozesmi, C; Baris, Y I
Abstract : All the 303 full time day workers in a carpet weaving factory were submitted to a physical examination, chest radiography, and vitalograph test, and answered a respiratory questionnaire. Fifty four healthy non-exposed subjects served as controls. Dust concentrations and concentrations of bacterial endotoxin were measured. Of the 303 workers, 259 (85.5%) had airway symptoms and 62 (20.5%) had maximum mid-expiratory flow (MMF) values of less than 60% compared with 9.2% of the controls. The symptoms in 68 workers (22%) were compatible with byssinosis and 36 of these workers underwent vitalography before starting work and after four hours work on Mondays when significant reductions of their FEV1 and MMF were found. Twenty one of these 36 workers were tested on Tuesday and no differences in these measurements were found between measurements before work started and four hours later. The airborne dust concentrations in the factory were high and bacterial endotoxin was found. These findings suggest that a large number of workers in this carpet weaving factory suffer from a disease indistinguishable from byssinosis even though wool is used almost exclusively, the only cotton being the warp. The finding of endotoxin together with the absence of cotton confirms the theory that "byssinosis" is due to bacterial endotoxin rather than to cotton per se.